Network of pharmaceutical education education institutions in ukraine in 90s of the 20TH century - Slipchuk Valentina (Borys Grinchenko Kyiv Metropolitan University, 2016)
Based on the analysis of archival material, the article presents a network of higher medical (pharmaceutical) educational institutions and medical (pharmaceutical) secondary schools in the 90s of 20th century;describes the plan of admission and features of the enrollment in the medical (pharmaceutical) secondary schools of the Ministry of Health of Ukraine on the specialty "pharmacy" for the professional training of the professional pharmacists in the regions of Ukraine in the 90s of 20th century;concludes that the amount of future pharmacists in medical (pharmaceutical) secondary schools in Ukraine on the basis of secondary school was twice as much as the amount of future pharmacists on the basis of junior secondary school;shows the network and the group of full-time course students in medical (pharmaceutical) secondary schools in the regions of Ukraine in the field professional training of health care industry specialists at the beginning of 1992-1993 academic year of 20th century; presents a network and group of medical (pharmaceutical) secondary schools on the specialty "pharmacy" in Ukraine in the 90s of 20th century;presents the network and a group of future professionals of pharmaceutical industry of Ukraine in the pharmaceutical faculties of medical (pharmaceutical) institutions of USSR at the beginning of the 1992-1993 academic year of 20th century; based on the analysis of archival sources it was concluded that in the 90s of 20th century the largest number of professionals of pharmaceutical industry (pharmacists) received the professional training at the Zhytomyr Protasevych College of Pharmacy, Stakhanov medical school and at the Kharkiv chemical and pharmaceutical medical school, and the largest number of professionals of pharmaceutical industry with higher pharmaceutical education received the professional training at the Zaporizhzhya medical institute and Ukrainian Pharmaceutical Academy.